The effectiveness of discovery learning module classification of materials and its changes to enhance critical thinking skills - Siti Rahmawati; Mohammad Masykuri; Sarwanto Sarwanto (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2021)
Abstract: This study aims to determine the effectiveness of natural science modules with discovery learning to enhance students' critical thinking skills in the topic of material classification and its changes. Critical thinking skills are one of the essential skills of the 21st century and are needed in various fields. Students with high critical thinking skills in general also can calculate various possibilities so that they can make decisions by applying logical thinking. Discovery learning trains students to build knowledge and develop student competencies independently. The research method was quasi-experimental with a nonequivalent pretest and posttest control groups design. The sampling technique employed was purposive sampling. The research instrument used a test of critical thinking skills. Data analysis was carried out with a different power test (t-test) to determine the difference between the experimental and control classes, and an N-Gain calculation was done to determine the effectiveness of the discovery learning module. The results showed a difference in critical thinking skills between the experimental class and the control class. The N-Gain result of the experimental class was 0.59, with a moderate category, and the control class was 0.31, with a moderate category.